Reforming defense and military policy-making in South Korea, 1987-2012 - Kühn, David (Reforming Civil-Military Relations in New Democracies, 2017)
In 1987, South Korea made the transition to electoral democracy after three decades of military rule. Democratic institutions started working sufficiently quickly after the end of authoritarian rule and civilian presidents succeeded in pushing the military out of politics by the mid-1990s. However, effective civilian control of defense and military policy was a long way to come and was only realized more than a decade after the transition with the establishment of the National Security Council. This chapter traces the development of civilian control over South Korea’s defense and military policy since the transition to democracy in 1987 to the end of President Lee Myung-bak’s term in office in 2012. It argues that the slow but ultimately successful establishment of civilian control over defense and military policy was the result of a protracted power struggle between civilian presidents and the military leadership who, despite contrary preferences, were reluctant to engage in open civil-military conflict, not least because of the ongoing security threat posed by North Korea. Democratization and the ‘Northern Threat’ also had tremendous impact on the country’s military effectiveness. Even though the transition to democracy did not fundamentally alter the threat situation in relation to North Korea, it did provide the political momentum to modernize defense and security policy, to strengthen the institutions necessary for an effective defense and military policy, and to ensure that the military remains well-funded, well-staffed, and well-equipped.
Gesehen am 05.12.2017